Scracth E-Modul: Inspecting Expert Validation - Yovita Yovita; Mery Berlian; Desi Nori Sahputri; Rian Vebrianto; Dilva Hardila; Musa Thahir (AL-ISHLAH: Jurnal Pendidikan, 2023)
Learning that is obtained quickly is always associated with technological developments. Scratch is a simple coding application that can be used in learning systems. This study aimed to analyze the validity of a Scratch-based E-Module learning media on the earth and the universe for grade 5 elementary schools, making the learning process more meaningful. This study used a research and development (RD) design with a quantitative descriptive approach where experts assessed the learning media that has been developed. The experts involved in this study were 9 people, including five lecturers and four certified teachers. Data were obtained using a validity test instrument to assess the E-module learning media that has been developed through meetings and explanations on how this learning media is operated, then, the experts filled the instrument out through the Google form prepared by researchers. Data were analyzed using SPPS version 23 and presented descriptively. The results show that the Scratch-Based E-Module has a validity value of 77% with very valid criteria. This demonstrates that the Scrach-Based E-Module is credible and useful for education, as stated by experts in the field. This Scratch-Based E-Module can therefore be implemented. Educators and scholars alike can benefit from this Scratch-Based E-Module.